Research in Computational Molecular Biology 15th Annual International Conference, RECOMB 2011, Vancouver, BC, Canada, March 28-31, 2011. Proceedings - Bafna, Vineet; Sahinalp, S. Cenk.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 15th Annual International Conference on Research in Computational Molecular Biology, RECOMB 2011, held in Vancouver, Canada, in March 2011. The 43 revised full papers were carefully reviewed and selected from 153 submissions. The papers cover a wide range of topics including molecular sequence analysis; recognition of genes and regulatory elements; molecular evolution; gene expression; biological networks; sequencing and genotyping technologies; genomics; population, statistical genetics; systems biology; imaging; computational proteomics; molecular structural biology.
Keywords: Computer science; Computer software; Database management; Artificial intelligence; Bioinformatics; Computer Science; Algorithm Analysis and Problem Complexity; Computational Biology/Bioinformatics.; Database Management; Computation by Abstract Devices; Artificial Intelligence (incl. Robotics).; Computer Science, general